Acquisitions Driven by Stock Overvaluation: Are They Good Deals? - FU, Fangjian (Institutional Knowledge at Singapore Management University, 2012)
Overvaluation might prompt a firm to use its stock to acquire a target whose stock is not as overpriced (Shleifer and Vishny (2003)). Though hypothetically desirable, these acquisitions in practice create little, if any, value for acquirer shareholders. Two factors often impede value creation: payment of a large premium to the target and lack of economic synergies in the acquisition. As a result, acquirer stock prices drop and target stock prices increase significantly during the bid process. The hypothetical benefits from the relative stock overvaluation of the acquirer to the target before the announcement largely disappear by the date of deal completion. Moreover, we find that overvaluation-driven stock acquirers suffer worse operating performance and lower long-run stock returns than control firms that are in the same industry, similarly overvalued at the same time, but have not pursued an acquisition. Our further findings suggest that stock overvaluation increases agency costs and the resulting actions potentially benefit managers more than shareholders (Jensen (2005)).